Behavioral measures to reduce non-adherence in renal transplant recipients: a prospective randomized controlled trial - Garcia, Márcia Fátima Faraldo Martinez [UNESP]; Bravin, Ariane Moyses [UNESP]; Garcia, Paula Dalsoglio [UNESP]; Contti, Mariana Moraes [UNESP]; Nga, Hong Si [UNESP]; Takase, Henrique Mochida [UNESP]; de Andrade, Luis Gustavo Modelli [UNESP] (International Urology And Nephrology, 2015)
Solid-organ transplant recipients present a high rate of non-adherence to drug treatment. Few interventional studies have included approaches aimed at increasing adherence. The objective of this study was to evaluate the impact of an educational and behavioral strategy on treatment adherence of kidney transplant recipients. In a randomized prospective study, incident renal transplant patients (n = 111) were divided into two groups: control group (received usual transplant patient education) and treatment group (usual transplant patient education plus ten additional weekly 30-min education/counseling sessions about immunosuppressive drugs and behavioral changes). Treatment adherence was assessed using ITAS adherence questionnaire after 3 months. Renal function at 3, 6, and 12 months, and the incidence of transplant rejection were evaluated. The non-adherence rates were 46.4 and 14.5 % in the control and treatment groups (p = 0.001), respectively. The relative risk for non-adherence was 2.59 times (CI 1.38-4.88) higher in the control group. Multivariate analysis demonstrated a 5.84 times (CI 1.8-18.8, p = 0.003) higher risk of non-adherence in the control group. There were no differences in renal function and rejection rates between groups. A behavioral and educational strategy addressing the patient's perceptions and knowledge about the anti-rejection drugs significantly improved the short-term adherence to immunosuppressive therapy.
Keywords: Graft rejection; Immunosuppression; Kidney transplantation; Medication adherence; Patient compliance